2004
DOI: 10.1039/b400663a
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of scattered light on a microchip flow cytometer with integrated polymer based optical elements

Abstract: Flow cytometry is widely used for analyzing microparticles, such as cells and bacteria. In this paper, we report an innovative microsystem, in which several different optical elements (waveguides, lens and fiber-to-waveguide couplers) are integrated with microfluidic channels to form a complete microchip flow cytometer. All the optical elements, the microfluidic system, and the fiber-to-waveguide couplers were defined in one layer of polymer (SU-8, negative photoresist) by standard photolithography. With only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
156
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(165 citation statements)
references
References 39 publications
9
156
0
Order By: Relevance
“…Since the SU-8 lids-based process involves the contact of two rigid surfaces and is not suitable for the bonding of large devices, there has been a demand to use a soft PDMS to seal SU-8 channels. 2,5 It is impossible to bond PDMS to SU-8 using any physical bonding method through a heat or solvent-based process because both cured PDMS and SU-8 are thermoset. Their molecular chain segments are constrained by their crosslinked networks and cannot diffuse into each other a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the SU-8 lids-based process involves the contact of two rigid surfaces and is not suitable for the bonding of large devices, there has been a demand to use a soft PDMS to seal SU-8 channels. 2,5 It is impossible to bond PDMS to SU-8 using any physical bonding method through a heat or solvent-based process because both cured PDMS and SU-8 are thermoset. Their molecular chain segments are constrained by their crosslinked networks and cannot diffuse into each other a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Many devices have been fabricated using SU-8 to take these advantages. SU-8 microfluidic channels were integrated with SU-8 optical waveguides in a single SU-8 layer fabricated through a one-shot process to create devices capable of microfluidic-photonic integrated flow cytometry, 2,3 and chemical assay. 4 Such devices were also directly integrated with optical fibers for the online monitoring of lactate, 5 and with electrochemical sensors for the detection of neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the demonstrated strategies, planar light guiding structures have demonstrated a high efficiency for light focusing within microsystems, with greatly reduced overall design complexity and modest increases in the total device footprint. [3][4][5][6][7][8][9][10]12 In the work conducted by Seo et al, for example, significant consideration was paid to complete device miniaturisation, where a disposable format was created that operated directly from an LED excitation source, with no additional devices required for light coupling. 9 Additionally, it was found that 2D Polydimethylsiloxane (PDMS) based microlenses confined the excitation emission within the chip and yielded no detectable excitation light orthogonal to the chip plane, resulting in a 7-fold increase in the detected fluorescence intensity from a sample of fluorescent nanospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Various light delivery and focusing components ranging from planar/3D lenses [3][4][5][6][7][8][9][10][11][12] to waveguides 13,14 have been demonstrated in integrated microfluidic and lab-on-a-chip devices. The primary advantages to such on-chip integration, in addition to the reduced size of key optical elements, are the self-alignment of the components and the ability to more tightly focus light onto microfluidic channels.…”
Section: Introductionmentioning
confidence: 99%
“…This design is simple and easily fabricated, leading several researchers to imitate it. 9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27] Unfortunately, the sample still comes into contact with the top and the bottom of the channel, which necessitates the addition of a dynamic or covalent coating to mitigate the propensity for fouling. [8][9][10][11]25 Also, cells and particles can appear at any depth from the top to the bottom of the channel, so high numerical aperture optics still cannot be used.…”
Section: Introductionmentioning
confidence: 99%